Reviewing for Beyond Behavior: An Editor's Guide for Submitting a Comprehensive and Meaningful Review. (April 2018) - Mooney, Paul; Ryan, Joseph B.
Reviewing manuscripts is an integral part of the publication process. Unfortunately, few scholars receive training in this skill. This article provides an overview of what it takes to conduct a quality review of a manuscript submission for a practitioner journal. The editors describe the manuscript types published by Beyond Behavior and a four-step approach for conducting a quality review that is informed by a review of literature and the editors' professional experience.